Stewards, Agents, and the Founder Discount: Executive Compensation in New Ventures - Wasserman, Noam (Academy of Management Journal, 2006)
Agency theory suggests that the interests of opportunistic, self-interested agents conflict with those of principals. Stewardship theory suggests instead that executives' interests are aligned with company interests and that executives are thus more intrinsically motivated than agency theory implies. This study develops hypotheses regarding the psychological and situational factors that affect the applicability of each theory to executive compensation. I tested hypotheses using a unique data set of 1,238 executives from 528 private companies. Results suggest significant differences between founder-stewards and nonfounder agents that diminish with company growth, and significant effects of equity ownership and outside rounds of financing.